Pengaruh Stres Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening: Studi Kasus Pada Karyawan PT. Karya Hevea Indonesia (KHI) Dolok Masihul - Arfah, Yenni; Yuliana, Yuliana; Misni, Misni (Management And Business Progress, 2024)
This research aims to determine the effect of work stress and work discipline on employee performance with job satisfaction as an intervening variable for employees at PT Karya Hevea Indonesia Dolok Masihul. The effects you want to know are direct or indirect effects. This type of research is explanatory research which explains cause and effect relationships between variables through hypothesis testing. From the results of this test it can be concluded that work stress has no significant effect on employee job satisfaction. Work discipline has a significant effect on employee job satisfaction. Job stress does not have a significant effect on employee performance. Work discipline has a significant effect on employee performance. Job satisfaction does not have a significant effect on employee performance. Job satisfaction cannot mediate the significant influence of work stress on employee performance. Job satisfaction cannot mediate the significant influence of work discipline on employee performance. through the mediation of job satisfaction.